Soluble CD83 Regulates Dendritic Cell–T Cell Immunological Synapse Formation by Disrupting Rab1a-Mediated F-Actin Rearrangement - Lin, Wei; Zhou, Shuping; Feng, Meng; Yu, Yong; Su, Qinghong; Li, Xiaofan (Frontiers in Cell and Developmental Biology, 2021)
Dendritic cell-T cell (DC-T) contacts play an important role in T cell activation, clone generation, and development. Regulating the cytoskeletal protein rearrangement of DCs can modulate DC-T contact and affect T cell activation. However, inhibitory factors on cytoskeletal regulation in DCs remain poorly known. We demonstrate that a soluble form of CD83 (sCD83) inhibits T cell activation by decreasing DC-T contact and synapse formation between DC and T cells. This negative effect of sCD83 on DCs was mediated by disruption of F-actin rearrangements, leading to altered expression and localization of major histocompatibility complex class II (MHC-II) and immunological synapse formation between DC and T cells. Furthermore, sCD83 was found to inhibit Rab1a-GTP activation, which further decreased colocalization and expression of LRRK2 and F-actin rearrangements in DCs, leading to the loss of MHC-II at DC-T synapses and reduced DC-T synapse formation. Further, sCD83-treated DCs alleviated symptoms of experimental autoimmune uveitis in mice and decreased the number of T cells in the eyes and lymph nodes of these animals. Our findings demonstrate a novel signaling pathway of sCD83 on regulating DC-T contact, which may be harnessed to develop new immunosuppressive therapeutics for autoimmune disease.